Pengaruh Penerapan Standar Akuntansi Pemerintahan, Sistem Pengendalian Internal Dan Kompetensi Staf Akuntansi Terhadap Kualitas Laporan Keuangan Pada Perangkat Daerah (PD) Kota Pariaman - Fathiah; Febrita Thresia Zen (CV. ITTC INDONESIA, 2024)
This research aims to determine the effect of implementating Government Accounting Standards, InternalControl System and Accounting staff Competence City Regional Apparatus. The data in this research was collected by distributing questionnaires to 30 employess, and then thereslts of the questionnnaire data were tested using validityand reliability test, data analysis techniques using classicassumption test, multiple linear regression analysis, coefficient of determination, and hypothesis testing.The results of the t test research show that (1) the application of Government Accounting Standards has a significant effect on the quality of financial reports in the Regional Apparatus of Pariaman City whit a t-count value of 13.132 and a significance value of 0.000 <0.05, (2)The Internal Control System has a significant effect on the quality of financial reports at the Pariaman City RegionalApparatus with a t-Count value of 10.397 and a significance value of 0.008 <0.05 and (3) Accounting staff competency has a significant effect on the quality of financial reports at the Pariaman City Government Regional Apparatus with a t-count value amounting to 9.597 and a significance value of 0.011,0.05. The result of the f test show that the implementation of Government AccountingStandards, Internal Control Systems, and Acconting Standards, Internal Control Systems, and Accounting staff competency simultaneously (Together) has an effect on the quality of financial reports in pariaman city Regional Apparatus with a calculated F Value of 61.732 and a significant value 0.000.05. Based on the results of the determination test, it can be seen that from the calculations the adjusted R Square value is 0.863. This shows that the large percentage of financial report quality (Y) thay can be explained by the independent variable implementation of Government Accounting Standards (X1), Internal Control System (X2), and Accounting staff competency (X3) is 86.3 %, while the remaining is 13.7 is influenced by other variables outside the model.